(untitled) (Baghdad Science Journal, 2013)
Five subsurface sections covering the entire length of the Jeribe Limestone Formation (Early Middle Miocene) were studied from four oilfields in northern Iraq. It is hoped to unravel this formation microfacies ; depositional environment; diagenetic attributes and their parental processes; and the relationship between these processes and the observed porosity patterns. The microfacies were found to include mudstone, wackestone, packstone, and grainstone, which have been deposited respectively in open platform, restricted platform, and edge platform which represent the lagoonal environment, while the deposits of the lower parts of the Jeribe formation especially in well Hamrin- 2 reflect a deeper fore slope environment. By using the lithofacies association concepts, the depositional model of the Jeribe Formation was built. From a reservoir point of view, the formation suffered from two groups of diagenetic processes. The first one includes the porosity destructive ones such as cementation; compaction; mechanical degradation; anhydritization; and silicification. The second group include porosity enhancers ones which to include dissolution; and dolomitization.